O TST e os doutrinadores jurídicos como agentes de novas noções contratuais do trabalho: um estudo sobre a terceirização. - Artur, Karen (Universidade Federal de São Carlos, 2004)
This research deals with the relation between the institutional issues and the labour market. Its main hypothesis is that the jurisprudence establishes new ways of work regulation and new contractual notions of labour. Its object is the study of the arguments of the ministers of the Tribunal Superior do Trabalho -TST (High Labour Court), and of the legal doctrine about new contractual forms of labour, especially the outsourcing. This study in based on a) analyses of socioeconomic particularly those related to work regulations; b) a balance of the doctrine in the main legal magazines; c) analysis of TST decisions from 1993 to 2003; d) 9 in-depth interviews with TST ministers and judges. In Brazil there is no specific law about outsourcing. Besides the determination of the legality of this contractual form by TST jurisprudence consolidate new rules of work. Law and Economy influenced each other in the process of building new rules and of defining notions licit outsourcing. This dissertation shows that the jurisprudence at the same time that is influenced by the new demands from a changing labour market imposes limits to the market through new notions of labour contract.
Keywords: Sociologia do trabalho; Tribunal Superior do Trabalho; Terceirização; Instituições do trabalho; OUTROS::CIENCIAS SOCIAIS